2021
DOI: 10.1111/epi.17006
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem mediates mental health outcomes in young people with epilepsy

Abstract: Summary Objective To evaluate the extent to which self‐esteem mediates the impacts of epilepsy‐specific and environmental factors on mental health outcomes in young people with epilepsy. Methods A prospective cohort of 480 young people with epilepsy and their families participated in five visits over 28 months. We collected data on clinical seizure burden, cognitive comorbidity, peer and parental support, self‐esteem, and self‐reported mental health symptoms. We used structural equation modeling to specify and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, the results of the current study revealed a significant negative association between self-esteem levels and naming, attention, and language functions. Although a recent study established a connection between low self-esteem and subjective memory problems, further research is needed to solidify this emerging topic (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the results of the current study revealed a significant negative association between self-esteem levels and naming, attention, and language functions. Although a recent study established a connection between low self-esteem and subjective memory problems, further research is needed to solidify this emerging topic (15).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions can negatively impact cognitive performance in PWTLE (13,14). Low self-esteem is also reported in focal epilepsy patients and appears to influence cognition, although further research is needed to clarify this relationship (15).…”
Section: Introductionmentioning
confidence: 99%
“…Schools, social media and advertising companies, and governments also have a responsibility to protect children and adolescents from harm and educate them on how to use social media safely and responsibly [33] The events that occurred in 2020/2021, such as the ongoing climate emergency, bushfires in Australia and the COVID-19 pandemic, reflect the human-caused environmental issues that young people are most concerned about and also exacerbate the mental health issues they have reported being at crisis point in 2019 [34] . A study found that environmental factors, such as perception of the surrounding environment, can significantly predict mental health indicators in young people aged 15 to 17 years [35] Another study found that self-esteem mediates the impact of epilepsyspecific factors and environmental factors on mental health outcomes in young people with epilepsy [36] It is very important to listen to adolescent views on mental health issues because these problems are common among young people, and exposure to stigmatization is an additional burden, leading to increased suffering [14], [17] Social media is a huge force in young people's lives with far-reaching effects on their development, and little research has been done on the impact of social media on young people's mental illness [24] The relationship between highly visual social media and young people's mental health remains unclear, and there is still little data exclusively examining highly visual social media [25] Social media use can negatively impact mental health and lead to addiction, but it can also help people to stay connected with friends and family during the COVID-19 pandemic [9], [10]. The impact of COVID-19 on young people's mental health has been a concern, and young people's discussions on social media about the impact of COVID-19 on their mental health have been analyzed thematically [37].…”
Section: Introductionmentioning
confidence: 99%